2019
DOI: 10.30794/pausbed.402715
|View full text |Cite
|
Sign up to set email alerts
|

Hedoni̇k Ve Faydaci Tüketi̇mi̇n Dürtüsel Ve Kompulsi̇f Satin Alma Üzeri̇nde Etki̇si̇

Abstract: Pazarlama yazınına göre tüketim, doğası gereği, bir taraftan faydacı diğer taraftan da hedonik boyutları olan ikili bir davranıştır. Araştırmanın amacı hedonik ve faydacı tüketimin, dürtüsel ve kompulsif satın alma davranışları üzerindeki etkisini incelemektir. Bu amaca ulaşmak için alanyazından elde edilen bilgiler ışığında Yapısal Eşitlik Modeli (YEM) oluşturulmuştur. Örnekleme yöntemi olarak, kümelere göre örnekleme yöntemi kullanılmıştır. Araştırma kapsamında, meslek yüksekokulunda öğrenim gören öğrenciler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
1
7
0
4
Order By: Relevance
“…Thus, it is possible that having strong impulses to buy, i.e., an increase in the tendency to IB, may cause a person who fails to control such impulses (compulsive buyer) to increase their tendency to CB. As a matter of fact, some studies have revealed that IBT has a positive effect on CBT (Bilgen Kocatürk & Eroğlu, 2022;Özdemir, 2022;Shehzadi et al, 2016;Tokgöz, 2019). As a result, it is possible to form the following hypothesis based on the above discussion: H3: Consumers' IBT increases their CBT.…”
Section: Relationships Between Se Ib and Cbmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, it is possible that having strong impulses to buy, i.e., an increase in the tendency to IB, may cause a person who fails to control such impulses (compulsive buyer) to increase their tendency to CB. As a matter of fact, some studies have revealed that IBT has a positive effect on CBT (Bilgen Kocatürk & Eroğlu, 2022;Özdemir, 2022;Shehzadi et al, 2016;Tokgöz, 2019). As a result, it is possible to form the following hypothesis based on the above discussion: H3: Consumers' IBT increases their CBT.…”
Section: Relationships Between Se Ib and Cbmentioning
confidence: 95%
“…Since CB is a behavior related to impulse control (Hague et al, 2016), IB likely affects CB. In this direction, it is possible to find studies in the literature showing that IB affects CB (Bilgen Kocatürk & Eroğlu, 2022;Özdemir, 2022;Shehzadi et al, 2016;Tokgöz, 2019). Therefore, the fact that IBT and CBT are not examined together in the context of FNE and SE is a problem regarding the necessity of addressing consumer behaviors holistically in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Benzer bir eğilim ülkemiz alanyazında da görülmektedir (örn. Arslan, 2015;Arslan ve Abdullah, 2016;Bozdağ ve Alkar, 2018;Karataş, 2011;Tokgöz, 2019). Dolayısıyla, bireylerin sosyal ve duygusal deneyimleri karşısında bir baş etme stratejisi olarak harcama davranışını ele alan çalışmalara ve ölçme araçlarına olan ihtiyaç sürmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Görüldüğü üzere, alanyazında kompulsif ve dürtüsel satın alma davranışlarına dair pek çok araştırma (örn. Sneath, Lacey, Kennett-Hensel, 2009;Sun, Wu ve Youn, 2004;Tokgöz, 2019) ve ölçüm aracı bulunmakla birlikte duygusal ve sosyal baş etme mekanizması olarak harcama davranışıyla ilgili çalışma ise oldukça kısıtlı sayıdadır. Dolayısıyla, ülkemizde de bu konuya ilişkin ölçeklerin uyarlanmasına veya geliştirilmesine de ihtiyaç olduğu görülmektedir.…”
Section: Introductionunclassified
“…Coşkun (2019) in his doctoral thesis study; developed a scale for the relationship between hedonic and utilitarian consumption behaviors and consumer ethnocentrism. On the other hand, Tokgöz (2019); states that utilitarian consumption has a significant and negative direct effect on impulsive and compulsive purchasing, and that consumers generally prefer products in hedonic terms and make impulsive and compulsive purchasing decisions. He also concluded that utilitarian and hedonic consumption had no mediating effect on the impact of compulsive buying.…”
mentioning
confidence: 99%